What’s African? Identifying Traits of African Security Governance - Chappuis, Fairlie; Kocak, Deniz; Sangar, Eric (Journal of Regional Security, 2018)
African and external approaches to security governance and reform have come to stress the importance of local, national and regional ownership, embodied at the national level by the concept of “local ownership” of Security Sector Reform and in the recourse to regional and sub-regional security mechanisms as “African solutions to African problems”. While a normative consensus on this idea seems to have emerged in the policy sphere, we ask what traits can be discerned in the national and regional discourses and practices of security governance that might be plausibly considered specifically African. This article thus explores the discourses and practices of attempts to link aspects of security governance to specific times and places at the national and regional levels in Africa. Tracing the discursive recourse to identity across four eras of modern African history, we argue that specifically African traits of security governance at national and regional levels can be discerned in institutional legacies of repression and poor security governance, as well as the discursive commitment to norms of human security at the regional level, as embodied in the African Peace and Security Architecture.